Air-stable Li5FeO4 additive enabled by carbon coating for energy-dense lithium-ion batteries - Canshang Liu; Hao Zhang; Weiwei Zhou; Xu Tian; Tiantian Zhang; Sicheng Niu; Jianing Li; Minglei Cao; Qin Wang; Fei Lv; Tangping Peng; Lijuan Tao; et al. (Nature Communications)
Abstract Li5FeO4 is a promising pre-lithiation additive for the positive electrode in lithium-ion batteries, offering the potential to enhance energy density. However, its susceptibility to air degradation presents a significant challenge for commercialization. In this study, we develop an effective carbon coating strategy utilizing pitch to improve the air stability of Li5FeO4. The coating process results in the formation of a compact carbon layer on the surface of Li5FeO4 particles, enabling the coated Li5FeO4 to retain a high specific capacity of 743.4 mAh g−1 after 72 h of exposure to air with 20% relative humidity. This retention represents 92.3% of its initial capacity and 85.7% of its theoretical maximum capacity. In contrast, uncoated Li5FeO4 undergoes rapid degradation, losing most of its electrochemical activity within just 4 h under identical conditions. Beyond improving air stability, the carbon coating enhances Li5FeO4’s specific capacity, rate capability, and cycling stability. To substantiate the practical application of carbon-coated Li5FeO4, we construct a pouch-type cell, which exhibits a 13.7% increase in energy density compared to the cell without the prelithiation additive. These findings collectively suggest that the carbon-coated Li5FeO4 represents a viable strategy for advancing the commercial deployment of this material in lithium-ion batteries.